2009
DOI: 10.1158/1055-9965.epi-09-0186
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Incidence of Colorectal Cancer Among Young Men and Women in the United States

Abstract: The recent, accelerated decline in colorectal cancer incidence rates has largely been attributed to an increase in screening rates among adults 50 years and older. We used data from 13 Surveillance, Epidemiology, and End Results cancer registries to report on colorectal cancer incidence trends from 1992 through 2005 among adults under age 50 years, for whom screening is not recommended for persons at average risk, by sex, race/ ethnicity, age, stage at diagnosis, and anatomic subsite. Overall, incidence rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
363
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 432 publications
(392 citation statements)
references
References 31 publications
24
363
1
4
Order By: Relevance
“…This percentage is similar to that reported in Jordan (20.2%) (Al-Jaberi et al, 2003), and Egypt (22%) (Veruttipong et al, 2012). Noteworthy, in western population, the incidence of the disease has increased in the 30-39 years group at an annual rate of 3% in men and 2% in women from 1992 to 2005 (Siegel et al, 2009) Some studies suggest that young CRC patients are diagnosed more frequently in advanced stage (Dozois et al, 2008). A publication based on the SEER database has demonstrated a higher frequency of stage III and IV disease in younger compared to older patients that was highly statistically significant (O'Connell et al, 2004a).…”
Section: Introductionsupporting
confidence: 87%
“…This percentage is similar to that reported in Jordan (20.2%) (Al-Jaberi et al, 2003), and Egypt (22%) (Veruttipong et al, 2012). Noteworthy, in western population, the incidence of the disease has increased in the 30-39 years group at an annual rate of 3% in men and 2% in women from 1992 to 2005 (Siegel et al, 2009) Some studies suggest that young CRC patients are diagnosed more frequently in advanced stage (Dozois et al, 2008). A publication based on the SEER database has demonstrated a higher frequency of stage III and IV disease in younger compared to older patients that was highly statistically significant (O'Connell et al, 2004a).…”
Section: Introductionsupporting
confidence: 87%
“…However, there have been reports about increasing incidence of CRC at a younger age (i.e. early-onset CRC) (Foroutan et al, 2008;Siegel et al, 2009). Therefore, investigation on the characteristics of patients with early-onset CRC is an urgent clinical demand in order to have a better screening strategy and early detection of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Siegel RL et al, [4] showed that in sharp contrast to the overall declining rates of CRC in the United States, incidence rates among adults younger than age 50 years are increasing. Although, the reasons for this rising incidence of CRC remain unclear and the relative incidence in persons under age 50 remains low, the increasing incidence in young people is a major public health concern [2].…”
Section: Discussionmentioning
confidence: 98%